Analysis of technological properties of heat-insulating aerated concrete (Международный научный журнал «Инженер», 2026)
The article briefly describes the historical development of aerated concrete production technology, modernmethods and the contribution of Uzbek scientists to this field, and also theoretically analyzes the relationshipbetween the thermal insulation properties of autoclaved aerated concrete and its composition, porous structureand density. The study compared aerated concrete samples with different compositions (standard, slag and sandwaste variants), analyzed their thermal conductivity coefficient (λ), density (ρ) and strength. According to theresults, the thermal insulation capacity of aerated concrete improved by 12–15% by adding industrial waste, andthe combination of slag and sand waste gave especially optimal indicators. In addition, the fact that the λ valueof aerated concrete is linearly dependent on its density was expressed through the mathematical model (λ = f(ρ)).